2015
DOI: 10.1017/s1368980015003079
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes diagnosis and nutrition facts label use among US adults, 2005–2010

Abstract: Objective: To assess the role of diabetes diagnosis as a potential teachable moment in nutrition facts label use among US adults. Design: Logistic regression analyses were conducted to examine the relationship between diabetes diagnosis status (diagnosed diabetes, undiagnosed diabetes, diagnosed prediabetes, undiagnosed prediabetes, no diabetes or prediabetes) and self-reported nutrition facts label use, adjusted by individual characteristics and survey design. Setting: Study sample came from the National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The percentage of individuals who reported frequently consulting nutritional information in this study (41%) was nearly identical to that observed in the general population of the United States (41.54%). [8] In Brazil, previous studies[1920] have investigated the use of nutrition labels among supermarket shoppers. However, these studies have used diverse categorizations of food label reading, which has hindered comparisons of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of individuals who reported frequently consulting nutritional information in this study (41%) was nearly identical to that observed in the general population of the United States (41.54%). [8] In Brazil, previous studies[1920] have investigated the use of nutrition labels among supermarket shoppers. However, these studies have used diverse categorizations of food label reading, which has hindered comparisons of the results.…”
Section: Discussionmentioning
confidence: 99%
“…[7] In the United States, people with diagnosed diabetes or prediabetes are more likely to report the use of food labels compared with those without these diagnoses. [8] On the other hand, a study conducted in Korea did not reveal a difference in the use of food labels by adults with hypertension, diabetes, or hyperlipidemia. [9] These dissimilarities may be because of the differences in the prevalence of risk factors, access to medical diagnosis, participation in annual health examinations, and sociocultural characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the definitions adopted by the Centers for Disease Control and Prevention 28 and An, 18 we classified survey respondents into 5 mutually exclusive categories based on their selfreported diabetes diagnoses and laboratory test results: diagnosed diabetes, diagnosed prediabetes, undiagnosed diabetes, undiagnosed prediabetes, and no diabetes/ prediabetes. Diagnosed diabetes was identified by the answer of "yes" to the interview question, "Have you ever been told by a doctor or health professional that you have diabetes or sugar diabetes?"…”
Section: Diabetes Measuresmentioning
confidence: 99%
“…If a new diabetes diagnosis could serve as a window of opportunity for health behavior promotion, targeting people with newly diagnosed diabetes will augment intervention effectiveness because they could be particularly receptive to change. 18 Moreover, these people often can be conveniently reached at clinics, hospitals, and other health care settings when attending appointments for their new diagnosis. Health care providers may seize this opportunity to offer on-site health behavior counseling shortly after delivering the diagnosis/treatment.…”
Section: Introductionmentioning
confidence: 99%